Autism - Allman, Toney (Diseases and disorders, 2010)
From the Publisher: The ailments and conditions that afflict people today can be confusing, disturbing, and painful-both emotionally and physically. The Diseases and Disorders series provides clear, careful explanations that offer readers and researchers insight into what these conditions are, what causes them, how people live with them, and the latest information about treatment and prevention. All volumes in the series include primary and secondary quotations, annotated bibliographies, detailed indexes, and lists of organizations to contact for additional information.